2013
DOI: 10.1109/tmag.2013.2241753
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Two-Phase Permanent Magnet Synchronous Motor Modeling for Torque Ripple Minimization

Abstract: This paper proposes a novel two-phase, two-pole, permanent magnet synchronous motor (PMSM) with dual U-core stator structure for torque ripple minimization. The proposed motor is modeled based on the conventional single-phase U-core PMSM with approximate output power and core dimension. Torque ripple in the novel motor can be reduced significantly due to 90 electrical angle phase shift in two sets of magnet pairs and 90 shift in two-phase excitation currents. Characteristics of both PMSMs such as back-EMF, cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…They concluded that the actual cogging torque and electromagnetic torque ripple can be reduced by one actual cogging period skew. In addition, [5], [6] also proposed novel motor structures for obtaining high performance motors by reducing torque ripples.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the actual cogging torque and electromagnetic torque ripple can be reduced by one actual cogging period skew. In addition, [5], [6] also proposed novel motor structures for obtaining high performance motors by reducing torque ripples.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, its efficiency and output density is high in comparison with other motors, and it can implement high efficiency and miniaturization. It is increasingly used in each field of the industry [3,4]. As development of power electronics advances control technology, control motors by vector control are applied to more fields to contribute to popularity thereof for precise control, for example, small AC servo motors.…”
Section: Introductionmentioning
confidence: 99%
“…Torque ripple is a critical concern in many high power PMSMs, and the existence of torque ripple degrades the control stability [4]. In order to alleviate these drawbacks and reduce current harmonics in steady state, the motor mathematical model is used to estimate the motor currents and thus to compensate for current harmonics caused by high switching frequency and to improve problems of current feedback delay and resolution limitation of digital control [5]. The predicted current estimator used in this paper obtains motor current feedback and accelerates the convergence with closed-loop control.…”
Section: Introductionmentioning
confidence: 99%
“…Block diagram of the proposed system. Equivalent circuit of the Y-connection PMSM.Transforming(5) and(6) into q-d stationary frame with (7), one obtains…”
mentioning
confidence: 99%